PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PERILAKU SOSIO-EMOSIONAL REMAJA (Studi Terhadap Siswa Perempuan Kelas X ADP SMK Muhammadiyah 2 Pekanbaru Tahun Ajaran 2014/2015) - Reizki Maharani; Zulfan Saam; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Behavior development in adolescence is marked by changes due to puberty, one of them, changes on socio-emotional behavior. Many students still reluctant to open in discussing matters related to puberty. They only know about physical changes. This research aims to know the effect of guidance service group toward socio-emotional behavior ofadolescence, especially the girl students in the X classat SMK Muhammadiyah 2 Pekanbaru. The method of this research is quasi experiment with one-group pretest–posttest designe. Subject of this research is 30 students who have low and medium socio-emotion. From the analysis of the data obtained can be seen that the value of thitung bigger than ttable, that is(30,08> 2,000). Thus Ho rejected and Ha accepted, its mean that from this research there is a significant differences between students socio-emotional behavior before and after guidance service group gave in first year students at ADP SMK Muhammadiyah 2 Pekanbaru.Keyword : Group guidance,Adolescence,Socio-Emotional